2011
DOI: 10.2176/nmc.51.694
|View full text |Cite
|
Sign up to set email alerts
|

Navigation-Guided Endoscopic Biopsy for Intraparenchymal Brain Tumor

Abstract: To evaluate the efficacy of intraparenchymal brain tumor biopsy using endoscopy and a navigation system (navigation-guided endoscopic biopsy) as a diagnostic tool, a case series of intraparenchymal tumor biopsies was reviewed. Navigation-guided endoscopic biopsy was applied in 9 cases, stereotactic needle biopsy in 16 cases, and open biopsy with or without navigation system in 34 cases. In all biopsy cases, 84.7% of biopsy points were sampled accurately, and 93.2% of diagnoses by biopsy were correct. Compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 29 publications
2
28
0
1
Order By: Relevance
“…12 There was no difference between endoscopic biopsies that employed navigation versus open or stereotactic biopsies with navigation, but there was a trend toward higher accuracy in neuroendoscopy, warranting further investigation with an appropriately powered study. 21 Brain shift did not present a problem for intraoperative accuracy in the studies included in this review 11,27,28 (Table 3). …”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…12 There was no difference between endoscopic biopsies that employed navigation versus open or stereotactic biopsies with navigation, but there was a trend toward higher accuracy in neuroendoscopy, warranting further investigation with an appropriately powered study. 21 Brain shift did not present a problem for intraoperative accuracy in the studies included in this review 11,27,28 (Table 3). …”
Section: Resultsmentioning
confidence: 86%
“…Of the reviewed studies, 4,12,14,21,2426 the most accurate target registration had a minimum error of 0.8 mm and mean error of 1.2 mm. 4 Registration accuracy was found to be study-dependent, with toleration of inaccuracies up to 3.5 mm reported.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In present endoscopic surgery instruments must avoid vital vessels and avert damage to tissue around the wound. 58,59) Here we choose the 0.7 mm needle, which is close to the mainstream diameter endoscope adopt by clinical surgery 60) and we did not observe any side-effect conditions, such as haemorrhage and death. Previous studies suggested that all kinds of trauma could influence neural function in a certain extent.…”
Section: Discussionmentioning
confidence: 99%